The influence of oil price shocks on China's macro-economy: A perspective of international trade - Shiyi Chen; Dengke Chen; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
International trade has been playing an extremely significant role in China over the last 20 years. This paper is aimed at investigating and understanding the relationship between China's macro-economy and oil price fromthis newperspective. We find strong evidence to suggest that the increase of China's price level, resulting fromoil price shocks, is statistically less than that of its main trade partners'. This helps us to understand the confused empirical results estimated within the SVAR framework and sheds light on recent data. More specifically, as for the empirical results, we find China's output level is positively correlated with the oil price, and oil price shocks slightly appreciate the RMB against the US dollar. Positive correlation between China's output and oil price shocks presumably results from the drop in China's relative price induced by oil price shocks, which is inclined to stimulate China's goods and service exports. The slight appreciation of the RMB could be justified by the drop in China's relative price, which is indicated by economic theory. Moreover, constructing a simple model, our new perspective also helps us to understand the recent fact that together with the dramatic surge of the world oil price, while the oil imports of the other major countries (especially the largest oil import country US) in the world steadily decline or remain stable, China's oil imports, in contrast, have kept rising steeply since the year 2004.
Keywords: F41; Q43; Q48; 330; Oil price shocks; International trade; China's macro-economy